Critical readings on Tang China - Kroll, Paul W. 1948- (Koninklijke Brill NV, 2018)
The Tang dynasty, lasting from 618 to 907, was the high point of medieval Chinese history, featuring unprecedented achievements in governmental organization, economic and territorial expansion, literature, the arts, and religion. Many Tang practices continued, with various developments, to influence Chinese society for the next thousand years. For these and other reasons the Tang has been a key focus of Western sinologists. This volume presents English-language reprints of fifty-seven critical studies of the Tang, in the three general categories of political history, literature and cultural history, and religion. The articles and book chapters included here are important scholarly benchmarks that will serve as the starting-point for anyone interested in the study of medieval China
4 vols.
Keywords: China / History / Tang dynasty, 618-907; China / Politics and government / 581-907; Chinese literature / Tang dynasty, 618-907 / History and criticism